(untitled) (History Journal «Jerónimo Zurita», 2024)
During the final centuries of the Middle Ages, the Crown of Castile strengthened its territorial control by conquering key enclaves in the southern Iberian Peninsula. Simultaneously, a historiographical discourse emerged, depicting Castilian monarchs as the legitimate heirs to the lost Visigothic kingdom. This legitimizing narrative is particularly evident in concise historiographical forms, where it is condensed and articulately expressed. This paper analyzes two texts from the latter half of the thirteenth century that exemplify this phenomenon: an account of the peninsular kings and a concise summary of Castilian history. These texts were subsequently reused in several later writings.